A new species of Pleroma (Melastomataceae) endemic to Chapada Diamantina, Bahia, Brazil - Freitas, Juliana Gomes; Berg, Cássio Van Den (Phytotaxa, 2016)
Pleroma rubrum (Melastomataceae, Melastomeae), a new shrubby species endemic to rocky outcrops of Chapada Diamantina, northeastern Brazil, is here described, illustrated and compared with closely related taxa. The new taxon is easily distinguished, within the Tibouchina pereirae species complex, by its quadrangular distal branches with a crown of long hirsute trichomes around nodes, leaves elliptic-lanceolate with reddish margins and petioles, reddish inflorescence and bracteoles, colored stipitate glands on all reproductive structures, except the pedoconnectives, involucral bracteoles, and urceolate capsules.